Influence of corpus callosum damage on cognition and physical disability in multiple sclerosis: a multimodal study. - Sara Llufriu (Public Library of Science (PLoS), 2012)
Background Corpus callosum (CC) is a common target for multiple sclerosis (MS) pathology. We investigated the influence of CC damage on physical disability and cognitive dysfunction using a multimodal approach. Methods Twenty-one relapsing-remitting MS patients and 13 healthy controls underwent structural MRI and diffusion tensor of the CC (fractional anisotropy; mean diffusivity, MD; radial diffusivity, RD; axial diffusivity). Interhemisferic transfer of motor inhibition was assessed by recording the ipsilateral silent period (iSP) to transcranial magnetic stimulation. We evaluated cognitive function using the Brief Repeatable Battery and physical disability using the Expanded Disability Status Scale (EDSS) and the MS Functional Composite (MSFC) z-score. Results The iSP latency correlated with physical disability scores (r ranged from 0.596 to 0.657, P values from 0.004 to 0.001), and with results of visual memory (r = -0.645, P = 0.002), processing speed (r = -0.51, P = 0.018) and executive cognitive domain tests (r = -0.452, P = 0.039). The area of the rostrum correlated with the EDSS (r = -0.442, P = 0.045). MD and RD correlated with cognitive performance, mainly with results of visual and verbal memory tests (r ranged from -0.446 to -0.546, P values from 0.048 to 0.011). The iSP latency correlated with CC area (r = -0.345, P = 0.049), volume (r = -0.401, P = 0.002), MD (r = 0.404, P = 0.002) and RD (r = 0.415, P = 0.016). Conclusions We found evidence for structural and microstructural CC abnormalities associated with impairment of motor callosal inhibitory conduction in MS. CC damage may contribute to cognitive dysfunction and in less extent to physical disability likely through a disconnection mechanism.